Does forest farm carbon sink projects affect agricultural development? Evidence from a Quasi-experiment in China. (1st June 2023) - Liu, Jian; Ren, Yanjun; Hong, Yu; Glauben, Thomas
Abstract: Forest Farm Carbon Sink (FFCS) projects are one of the effective ways to achieve carbon neutrality and mitigate global warming. Though the existing literature has widely discussed the effect of FFCS on the allocation of agricultural factors, such as land, labor employment structure and income structure, little is known about whether FFCS projects could have an effect on agricultural development. Based on the panel data of 140 counties in Sichuan province, China, from 2002 to 2018, we examined the causal effect on agricultural total factor productivity (TFP), and revealed their dynamic effect and underlying mechanisms. Propensity score matching and the difference in difference (PSM-DID) method were used to address the endogeneity problem of FFCS implementation. Results showed that FFCS projects increased agricultural TFP by 1.7%–2.4%. Health, saving and industrial structure were the important channels through which FFCS projects affect agricultural TFP. Our findings suggest that policies promoting FFCS projects can increase agricultural TFP while achieving environmental goals—a win-win situation. Highlights: The causal effect of FFCS projects on agricultural development was examined. A theoretical framework was constructed to quantify FFCS projects and agricultural development. FFCS projects significantly increased agricultural TFP by 1.7%–4.9%. FFCS projects affect agricultural TFP in short term but not in the medium and long term. Health, saving and industrial structure were the important channels underlying the effect of FFCS projects.